2017
DOI: 10.1371/journal.pone.0175097
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after transplantation of pediatric liver grafts from donation after circulatory death donors

Abstract: BackgroundLiver grafts from donation after circulatory death (DCD) donors are increasingly accepted as an extension of the organ pool for transplantation. There is little data on the outcome of liver transplantation with DCD grafts from a pediatric donor. The objective of this study was to assess the outcome of liver transplantation with pediatric DCD grafts and to compare this with the outcome after transplantation of livers from pediatric donation after brain death (DBD) donors.MethodAll transplantations per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…For children, the use of DCD grafts is still controversial and the available data are limited to small series. 3,4 To improve outcome of DCD liver transplantation, ex situ HMP is increasingly used as an alternative strategy for organ preservation, with the supplemental value of providing oxygen to the graft during preservation. 5 The initial experience in adults has demonstrated that end-ischemic HMP provides better preservation of DCD liver grafts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For children, the use of DCD grafts is still controversial and the available data are limited to small series. 3,4 To improve outcome of DCD liver transplantation, ex situ HMP is increasingly used as an alternative strategy for organ preservation, with the supplemental value of providing oxygen to the graft during preservation. 5 The initial experience in adults has demonstrated that end-ischemic HMP provides better preservation of DCD liver grafts.…”
Section: Introductionmentioning
confidence: 99%
“…This case report describes the first successful transplantation of a pediatric DCD liver graft after ex situ oxygenated HMP. There are only a few descriptions of pediatric liver transplantations with grafts from DCD donors in the current literature 3,4,9. Hong et al reported a matched case-control study of 7 DCD liver transplantations in pediatric patients with excellent long-term outcomes 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increase in ischemic cholangiopathy using DCDD organs, pediatric DCDD OLT's acceptable outcomes warrant its expanded implementation given insufficient DBD organ availability. Providing further justification for the increased use of pediatric DCDD allografts, van Rijn, et al [4] reports equivalent patient and allograft survival rates between recipients of pediatric DCDD (warm ischemia time < 30 minutes) and DBD livers, with comparable incidence of biliary or non-biliary complications.…”
Section: Optimization Of Donor Liver Supplymentioning
confidence: 99%
“…(21) Although 1 retrospective study reported similar graft and patient survival of pediatric DCD livers when compared with age-matched DBD donors, there remains a paucity of data evaluating the use and overall outcomes of pediatric DCD allografts. (22) The purpose of this study was to examine trends of national DCD allograft recovery and associated longterm outcomes through analysis of the OPTN database and, additionally, to investigate DCD listing and allocation trends relative to age. We hypothesized that younger pediatric DCD livers are being recovered at a disproportionately low rate when compared with matched adult DCD livers.…”
mentioning
confidence: 99%